Reflections on an action-oriented workshop: How can more of our professors be Māori and Pasifika? - Hine Funaki; Avery Smith; Nayantara Sheoran Appleton; Emily Beausoleil; Meegan Hall; Liana MacDonald; Amanda Thomas (University of Johannesburg, 2021)
There is a chronic underrepresentation of Māori and Pacific academics in our university sector in Aotearoa New Zealand. Sitting behind the disparity are a range of practices that support some groups in Aotearoa New Zealand to succeed and move more freely through higher education institutions than others. In response to scholarship highlighting this issue, a collective of students and staff at Te Herenga Waka | Victoria University of Wellington came together to organise an action-oriented workshop to draw attention to ways that universities are governed through power relations. Attention was also paid to mitigating power imbalances in the organisation, format, and delivery of the event, and between attendees, presenters, and event facilitators from dominant and non-dominant ethnic and cultural groups. This reflection piece is not so much a recounting of the event itself but rather an opportunity to share with the wider academic world ways in which the collective attempted to hold our university accountable for failing in their responsibilities to the people on whose ancestral lands they exist.